Does Pharmacotherapy Support or Hinder Psychotherapy? Questions, Problems, Mastery and Expertise - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
While effective psychotropic medications have been introduced more than 50 years ago and cognitive behavior therapy (CBT) as the most evidence-based psychotherapy was introduced for depression about 40 years ago substantial uncertainty continues to exist about the combination of pharmacotherapy and psychotherapy. On the one hand both forms of therapy had to first prove their effectiveness individually, and while there is no doubt that both therapeutic approaches are beneficial in some way the quest is ongoing to refine both the psychotherapeutic treatment protocols as well as the pharmacological agents as monotherapies. On the other hand, in many health systems there has often been a divide between the clinician, who prescribes medication often a general practioner or psychiatrist - and the clinician who delivers psychotherapy - often a psychologist or trained nurse. This divide may have contributed to the relative paucity of studies regarding combined treatment although in clinical reality most patients starting psychotherapy have had some experience with pharmacological treatments. This article focuses on the evidence regarding combination therapy in depression and in anxiety disorders and attempts to give some practical guidelines for clinical management.
Keywords: Pharmacotherapy; psychotherapy; cognitive behavior therapy; combined treatment; COGNITIVE-BEHAVIORAL THERAPY; RANDOMIZED CONTROLLED-TRIAL; ANXIETY DISORDERS; PSYCHOLOGICAL TREATMENTS; SEVERE DEPRESSION; PANIC DISORDER; COMBINATION; METAANALYSIS; MEDICATIONS; EFFICACY